Chemical-Mineralogical study of the ferrosialitic lateritic profiles in the Teneme, Farallones and Cayo Guam sectors in North East Cuba - Njila, Tendai (2016)
The results of a chemical-mineralogical study on the ferrosialitic lateritic weathering profiles are presented. Analysis was done using X Ray Fluorescence and Diffraction. The chemical composition of these profiles reflects a typical pattern normally observed within such weathering crusts. The sesquioxides of aluminium, iron are concentrated in the upper parts of the profiles as a result of the leaching of alkalis, alkaline-earth elements, and to a lesser extent, silica. Ferrosialitic lateritic profiles formed on Cretaceous and Paleogene islands arcs consist of secondary minerals such as gibbsite, kaolinite, goethite, hematite and montmorillonite, while those associated with basic and volcanogenic-sedimentary rocks of ophiolitic affinity in Cayo Guam are composed of gibbsite and iron oxides. This study brings new chemical-mineralogical information on the ferrosialitic lateritic profiles associated with rocks of oceanic nature in north-eastern Cuba, which will help in the exploration for industrial minerals, and rocks and their application in industry.